2014
DOI: 10.1128/aac.01263-13
|View full text |Cite
|
Sign up to set email alerts
|

In Silico Prediction and Experimental Evaluation of Furanoheliangolide Sesquiterpene Lactones as Potent Agents against Trypanosoma brucei rhodesiense

Abstract: dAs a continuation of our earlier study on the in vitro antiprotozoal activity of 40 natural sesquiterpene lactones (STLs), we extended the set of tested compounds from our laboratories to 59. On the basis of this extended data set, further enriched by literature data for 10 compounds tested under the same conditions, our quantitative structure-activity relationship (QSAR) analyses for activity against T. brucei rhodesiense (etiologic agent of human African trypanosomiasis, or sleeping sickness) were continued… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(69 citation statements)
references
References 23 publications
2
66
0
1
Order By: Relevance
“…The bioactivity data obtained in this study complements previous data on sesquiterpene lactones obtained in our lab. Elemanolide type sesquiterpene lactones have not previously been reported to have anti-trypanosomal activity, therefore that the data reported here also broaden the knowledge on structure–anti-trypanosomal activity relationships of sesquiterpene lactones [ 10 , 28 ].…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…The bioactivity data obtained in this study complements previous data on sesquiterpene lactones obtained in our lab. Elemanolide type sesquiterpene lactones have not previously been reported to have anti-trypanosomal activity, therefore that the data reported here also broaden the knowledge on structure–anti-trypanosomal activity relationships of sesquiterpene lactones [ 10 , 28 ].…”
Section: Discussionsupporting
confidence: 54%
“…Natural products from plants, microorganisms and marine organism have a long and successful tradition as drugs or as leads in drug development [ 7 , 8 ]. In continuation of our ongoing search for new anti-trypanosomal agents in plants [ 9 , 10 , 11 , 12 ], we set out to investigate the activity of Vernonia lasiopus O. Hoffm. (Asteraceae) and its secondary metabolites against protozoan parasites.…”
Section: Introductionmentioning
confidence: 99%
“…For example, chemotaxonomic studies of the Asteraceae family have been performed using self‐organizing maps and neural networks, and QSAR studies have identified some sesquiterpene lactones with promising activities against infectious diseases, such as 4,15‐isoatripicolide tiglate, which was the most potent structure against T. brucei in a purely in silico study of 1750 SLs. This result was subsequently validated in an in vitro test (IC 50 =1.5 μ m ) . Some studies have shown how ligand‐based QSAR models complement structure‐based approaches by boosting the prediction performances when used in tandem; in addition, ligand‐based modeling has been used to select a more appropriate protein conformation for docking and assess the reliability of the docking experiment .…”
Section: Introductionmentioning
confidence: 84%
“…Sesquiterpene lactones (STLs) have been demonstrated to have potent and, in many instances, selective toxicity against protozoan parasites, the etiological agents of several neglected tropical diseases (NTDs). Recently, furanoheliangolide-type STLs, characterized by the presence of Michael-acceptor structural motifs, were demonstrated to be endowed with high-level in vitro activity against Trypanosoma brucei rhodesiense [55]. In their work, Lenz and colleagues [56] studied the molecular basis of the activity of different furanoheliangolides.…”
Section: Inhibition Of Trypanothione Reductase By 415-iso-atriplicolmentioning
confidence: 99%